Implementing the Merdeka Curriculum through Joyful Learning Approaches in Early Childhood Education - Durotun Nafisah; Khotimatus Sholikhah; Winnuly Winnuly (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of the Joyful Learning-based Independent Curriculum in early childhood learning in playgroups. Child-centered, enjoyable, non-pressuring early childhood learning that is in line with children's developmental characteristics is crucial. The study used a descriptive qualitative approach with a case study. The research subjects included the principal, group B teachers, and students aged 4–5 years. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was obtained through triangulation of sources and techniques. The results showed that the implementation of the Joyful Learning-based Independent Curriculum at KB Darul Ilmi took place through a curriculum orientation that was in line with the institution's vision, flexible learning planning, the use of varied media, the application of a center model, providing activity choices, and the implementation of child-centered learning. Teachers acted as facilitators who created a safe atmosphere, provided positive reinforcement, instilled character, and conducted authentic assessments through observation, anecdotal notes, photo documentation, work results, and narrative reports. Supporting factors for implementation include principal leadership, teacher competence, instructional media, and a conducive learning environment. Key challenges include parents' perceptions of instant literacy, time management, and classroom structure.